Development of aerial and belowground tubers in potato is governed by photoperiod and epigenetic mechanism - Kondhare, Kirtikumar R.; Kumar, Amit; Patil, Nikita S.; Malankar, Nilam N.; Saha, Kishan; Banerjee, Anjan K. (Plant Physiology, 2021)
Plants exhibit diverse developmental plasticity and modulate growth responses under various environmental conditions. Potato (Solanum tuberosum), a modified stem and an important food crop, serves as a substantial portion of the world's subsistence food supply. In the past two decades, crucial molecular signals have been identified that govern the tuberization (potato development) mechanism. Interestingly, microRNA156 overexpression in potato provided the first evidence for induction of profuse aerial stolons and tubers from axillary meristems under short-day (SD) photoperiod. A similar phenotype was noticed for overexpression of epigenetic modifiers-MUTICOPY SUPRESSOR OF IRA1 (StMSI1) or ENAHNCER OF ZESTE 2 (StE[z]2), and knockdown of B-CELL-SPECIFIC MOLONEY MURINE LEUKEMIA VIRUS INTEGRATION SITE 1 (StBMI1). This striking phenotype represents a classic example of modulation of plant architecture and developmental plasticity. Differentiation of a stolon to a tuber or a shoot under in vitro or in vivo conditions symbolizes another example of organ-level plasticity and dual fate acquisition in potato. Stolon-to-tuber transition is governed by SD photoperiod, mobile RNAs/proteins, phytohormones, a plethora of small RNAs and their targets. Recent studies show that polycomb group proteins control microRNA156, phytohormone metabolism/transport/signaling and key tuberization genes through histone modifications to govern tuber development. Our comparative analysis of differentially expressed genes between the overexpression lines of StMSI1, StBEL5 (BEL1-LIKE transcription factor [TF]), and POTATO HOMEOBOX 15 TF revealed more than 1,000 common genes, indicative of a mutual gene regulatory network potentially involved in the formation of aerial and belowground tubers. In this review, in addition to key tuberization factors, we highlight the role of photoperiod and epigenetic mechanism that regulates the development of aerial and belowground tubers in potato.

Polycomb group methyltransferase StE(z)2 and deposition of H3K27me3 and H3K4me3 regulate the expression of tuberization genes in potato - Kumar, Amit; Kondhare, Kirtikumar R.; Malankar, Nilam N.; Banerjee, Anjan K. (Journal of Experimental Botany, 2021)
Polycomb repressive complex (PRC) group proteins regulate various developmental processes in plants by repressing target genes via H3K27 trimethylation, and they function antagonistically with H3K4 trimethylation mediated by Trithorax group proteins. Tuberization in potato has been widely studied, but the role of histone modifications in this process is unknown. Recently, we showed that overexpression of StMSI1, a PRC2 member, alters the expression of tuberization genes in potato. As MSI1 lacks histone-modification activity, we hypothesized that this altered expression could be caused by another PRC2 member, StE(z)2, a potential H3K27 methyltransferase in potato. Here, we demonstrate that a short-day photoperiod influences StE(z)2 expression in the leaves and stolons. StE(z)2 overexpression alters plant architecture and reduces tuber yield, whereas its knockdown enhances yield. ChIP-sequencing using stolons induced by short-days indicated that several genes related to tuberization and phytohormones, such as StBEL5/11/29, StSWEET11B, StGA2OX1, and StPIN1 carry H3K4me3 or H3K27me3 marks and/or are StE(z)2 targets. Interestingly, we observed that another important tuberization gene, StSP6A, is targeted by StE(z)2 in leaves and that it has increased deposition of H3K27me3 under long-day (non-induced) conditions compared to short days. Overall, our results show that StE(z)2 and deposition of H3K27me3 and/or H3K4me3 marks might regulate the expression of key tuberization genes in potato.
Keywords: ChIP-sequencing; Epigenetics; PcG; photoperiod; polycomb repressive complex; potato tuberization; short-day; Solanum tuberosum; StE(z)2